PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH COMMUNICATION TERHADAP KEPUTUSAN PENGGUNAAN JASA (Studi pada Konsumen Ella Skincare Surakarta) - Nurny Sofwah Rifqiyani; Apriatni Endang Prihatini (Universitas Diponegoro, 2019)
Public awareness of the importance of beauty care has been increasing, therefore there are many beauty clinics appear, one of them is Ella Skincare. In the last three years Ella Skincare hasn’t been able to reach Top Brand Market Share of beauty clinic in Indonesia. In addition, during the period of 2016-2018, there were complaints from customer regarding the quality of service and product. The quality of service and word of mouth communication are factors that influence consumers' decisions to use the services. This research aims to know the influence of service quality and word of mouth communication on service use decisions. The type of research is explanatory research and sampling tecnique used is non probability sampling with purposive sampling and accidental sampling of 100 respondents. The data collection uses questionnaires and googleforms. This research uses kuantitative analysis with validity test, reliability test, correlation coefficient, coefficient of determination, simple regression, multiple regression, t test and F test helped by Microsoft Excel and SPSS version 16. The results of the study show that the quality of service variables and word of mouth communication have a strong, significant and positive influence on the decision to use. The advice given to company is to improve service quality and creating a good experience in order to make consumers want to communicate their experience to user candidates of Ella Skincare.